ACHIEVEMENTS AND CHALLENGES IN THE EDUCATIONAL REALM IN SAUDI ARABIA - Annemarie Profanter (European Scientific Journal, ESJ, 2014)
Often the greatest symbol of national education is a university. While the first University in Saudi Arabia was King Saud University in Riyadh est. 1957, Saudi Aramco has served as a ―defacto university‖ setting for thousands of Saudi‘s from all over the Kingdom. While for years there were just a handful of government universities catering to a minority of high school graduates, the number of private universities is helping to take up the slack such as Prince Mohammad Bin Fahd University in the Eastern Province which opened its doors in 2006 and was the first to enroll both male and female students in separate facilities. Those modern higher education institutions are being surrounded by a conservative Muslim society that holds many challenges one of which is the waste of the female potential for the societal development. With a reported unemployment rate for women of 21.7% and of men 7.6%, there is a large discrepancy in gender differentiated unemployment. It is often pointed to three conditions that must be met before women can be fully integrated into the wage labor force: need, opportunity and ability. While in the educational realm women are gaining grounds, Saudi Arabia remains a very traditional, conservative society where school to work transition remains a major challenge. However, in order to fully implement the concept of Saudization these traditional gender roles need to be renegotiated.